Household Waste Management into Organic Fertilizer in Tangkas Village, Klungkung - Situmeang, Yohanes Parlindungan; Mahardika, Ida Bagus Komang; Widyawati, Ida Ayu Trisna; Wunda, Dinasti Dada (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Tangkas Village, located in Klungkung District, Bali, holds significant potential for organic waste utilization through the activities of the Satwa Winangun Livestock Farmer Group. This group processes cow manure and household waste into organic fertilizer. Despite contributing to waste management and sustainable agriculture, several challenges remain, including suboptimal fertilizer quality, limited application of appropriate technologies, and issues related to packaging, marketing, and product certification. This study aims to (1) improve the quality of organic fertilizer derived from household waste and cow manure through technology transfer and the use of local materials, and (2) enhance the product's added value through business management assistance, marketing strategies, packaging improvements, and certification facilitation. The research outcomes are expected to contribute to increased agricultural productivity, more efficient waste management, and improved competitiveness of organic fertilizer products at both local and regional levels. Contribution to Sustainable Development Goals (SDGs)SDG 2 (Zero Hunger)SDG 8 (Decent Work and Economic Growth) SDG 12 (Responsible Consumption and Production)SDG 13 (Climate Action).